Aproximaciones a una propuesta de educación para la paz con perspectiva de género para el caso del postconflicto colombiano (2020)
Women in Latin America have been victims of violence in the armed conflict; so, as a response to the violence experienced, some have chosen to participate in peacebuilding. In Colombia, women -in the peace agreement context- managed to include the mainstreaming of the gender approach. This fact constituted a historical milestone that invited reflection on the role of women in peacebuilding and the appropriate educational training conditions to enhance their leadership, in the way to enduring and sustainable peace. These issues justified this research on education, gender, and peace, which proposed to design an educational training proposal for the construction of healthy, equitable, and peaceful gender relationships in the post-conflict in Colombia. This paper shows the results of the investigation exploratory phase, and it explains the perception that 134 men and women ex-FARC combatants had in Colombia in 2018, regarding the mainstreaming of the gender perspective in the final peace agreement.